Evaluation of city sustainability using the HGRW method: A case study of urban agglomeration on the West Side of the Straits, China. (15th July 2022) - Dong, Qiankun; Yi, Pingtao; Li, Weiwei; Wang, Lu
Abstract: City sustainability evaluation has a positive effect on guiding urban economy toward efficiency, stability and innovation with minimal resource consumption. This paper evaluated the sustainability level of Urban Agglomeration on the West Side of the Straits (WSS) in China from three dimensions: economy, society, and environment. We proposed a weighting method based on the hybrid GRA (HGRW) to calculate indicator weights, which considers the interaction between indicators through the similarity of curves, especially the annual increment curves. Evaluation results showed the sustainability level of WSS was not high with regional polarization and imbalance. Five core cities ranked in the top five, of which Xiamen performed best with an evaluation value over 0.65. The development of three sustainability dimensions was uncoordinated. Most cities were in the status of near coordination or primary coordination. The factors that drive and hinder city sustainability were related to economic and social aspects, such as investment in fixed assets, worker's wages, and education investment. Based on these findings, we made targeted suggestions for the local development planning.